2015
DOI: 10.1144/sp425.1
|View full text |Cite
|
Sign up to set email alerts
|

Palaeomagnetic results from the fold and thrust belt of the Western Carpathians: an overview

Abstract: The Western Carpathians are separated into an Outer and Inner Carpathians (both comprising several nappe systems) by the extremely narrow and highly deformed Pieniny Klippen Belt. The main phase of deformation and thrusting took place during the Late Cretaceous in the Inner Carpathians, at the end of Cretaceous–Paleocene in the Pieniny Klippen Belt and in the Miocene in the Outer Carpathians. In this paper a large amount of palaeomagnetic results of different quality available from several nappe stacks and fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 64 publications
2
32
0
Order By: Relevance
“…How ever, any re con struc tion of palaeostress states is com pli cated by the Mio cene block ro ta tion of the whole Western Carpathians (e.g., Fodor, 1995;Marko et al, 1995;Márton et al, 2016). Con se quently, changes of palaeostress ori en tation in the area were likely caused by a com bi na tion of the clock wise ro ta tion of the stress field and the coun ter clock wise (CCW) ro ta tion of the ALCAPA microplate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…How ever, any re con struc tion of palaeostress states is com pli cated by the Mio cene block ro ta tion of the whole Western Carpathians (e.g., Fodor, 1995;Marko et al, 1995;Márton et al, 2016). Con se quently, changes of palaeostress ori en tation in the area were likely caused by a com bi na tion of the clock wise ro ta tion of the stress field and the coun ter clock wise (CCW) ro ta tion of the ALCAPA microplate.…”
Section: Discussionmentioning
confidence: 99%
“…De for ma tion structures of this stage are not ob served in the Bartonian-Oligo cene de pos its of the Cen tral Carpathian Paleogene Ba sin, there fore the first palaeostress state re corded must have oc curred earlier, most prob a bly dur ing the late Mid dle Eocene. There fore, con sid er ing a Mio cene block ro ta tion of the West ern Carpathian of c. 50-60° (Márton et al, 2016), the orig i nal ori en ta tion of the main com pres sive palaeostress axis should have been in the NNW-SSE di rec tion (Fig. 10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Márton et al (2009) studied the paleomagnetism and the magnetic aniso tropy of the Paleogene (subordinately Lower Miocene) grey clay, silt and mudstones from the Magura and the Silesian Nappes. Their results pointed to a general 50° CCW rotation of the Magura nappe and of the central and eastern segment of the Silesian nappe, and somewhat larger for the western part of the Silesian Nappe), which must have taken place after the Oligocene (Márton et al 2016). The AMS (anisotropy of magnetic susceptibility) measurements revealed that the magnetic foliation was due to compaction and the magnetic lineation to weak compressional deformation.…”
Section: Introductionmentioning
confidence: 97%
“…1); the Western Carpathians (Márton et al 2015) and the Western and Central Mediterranean arcs . In both cases, synthetic and robust palaeomagnetically deduced VARs are used to constrain the kinematic and geodynamic evolution in these regions.…”
mentioning
confidence: 99%